2020
DOI: 10.1039/d0ta07189g
|View full text |Cite
|
Sign up to set email alerts
|

Photo-driven growth of a monolayer of platinum spherical-nanocrowns uniformly coated on a membrane toward fuel cell applications

Abstract: Membrane electrode assemblies (MEAs) serve as the core units of polymer electrolyte membrane fuel cells (PEMFCs) and are regularly fabricated by painting a slurry of commercial Pt/C onto membrane, leading...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…It can be seen that the model achieved good agreement with the experimental data using the parameters in Table 2. To achieve the agreements, it was found that the effective exchange current density ai 0,c is much smaller than the value of traditional CLs ($10 4 A m À3 for 10 mm thick CLs 25 ), which is possibly due to the small electrochemically active surface area (ECSA, $5 m 2 g Pt À1 ) as measured experimentally 27 versus that of conventional CLs ($30-50 m 2 g Pt À1 ). 18 In addition, an equivalent ionomer content 3 m of 0.0304 was adopted in the CLs, which is much lower than that of common CLs ($0.23 (ref.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…It can be seen that the model achieved good agreement with the experimental data using the parameters in Table 2. To achieve the agreements, it was found that the effective exchange current density ai 0,c is much smaller than the value of traditional CLs ($10 4 A m À3 for 10 mm thick CLs 25 ), which is possibly due to the small electrochemically active surface area (ECSA, $5 m 2 g Pt À1 ) as measured experimentally 27 versus that of conventional CLs ($30-50 m 2 g Pt À1 ). 18 In addition, an equivalent ionomer content 3 m of 0.0304 was adopted in the CLs, which is much lower than that of common CLs ($0.23 (ref.…”
Section: Resultsmentioning
confidence: 96%
“…1 Photo-driven method for low-Pt-loading CL fabrication. 27 The -CF2chain of the PFSA membrane is included in the gray area of the zoom-in plot. on the conservation laws of mass, momentum, species, energy, and charges in conjunction with the electrochemical kinetics in the CLs.…”
Section: The Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each peak appears consistently with the fcc-Pt (JCPDS #04-0802), indicating the metallicity of Pt in the catalyst. , The inset is the TEM image of magnetron-sputtered Pt nanoparticles. The high-magnification TEM image clearly shows that the d -spacing between the adjacent lattice fringes is 2.3 Å, which is attributed to the planes of fcc bulk Pt ,,, (refer Supporting Information-5 for more TEM images).…”
Section: Resultsmentioning
confidence: 99%
“…In practice, Pt nanoparticles, instead of planar Pt, are usually used as electrocatalysts to improve electrochemical kinetics. At present, several approaches have been attempted to reduce the O 2 transport resistance in the ionomer–Pt interface, including removing the ionomer phase in CLs ( e.g ., 3M’s nanostructured thin film (NSTF)) and adding other species ( e.g ., ionic liquid molecules) into the ionomer. …”
mentioning
confidence: 99%